Controllable synthesis of Co3O4 nanocrystals as efficient catalysts for oxygen reduction reaction. (30th January 2018) - Li, Baoying; Zhang, Yihe; Du, Ruifeng; Liu, Lei; Yu, Xuelian
Abstract: The electrochemical oxygen reduction reaction (ORR) has received great attention due to its importance in fuel cells and metal–air batteries. Here, we present a simple approach to prepare non-noble metal catalyst-Co3 O4 nanocrystals (NCs). The particle size and shape were simply controlled by different types and concentrations of metal precursor. Furthermore, different sizes and shapes of Co3 O4 NCs are explored as electrocatalysts for ORR, and it has been observed that particles with a similar shape, and smaller particle size led to greater catalytic current densities because of the greater surface area. For particles with a comparable size, the shape or crystalline structure governed the activity of the electrocatalytic reactions. Most importantly, the 9 nm-Co3 O4 were demonstrated to act as low-cost catalysts for the ORR with a similar performance to that of Pt catalysts.